The Effect of Sustainability Disclosure and Earning Quality on Stock Prices with Dividend Policy as A Moderation Variable at PT Indo Tambangraya Megah Tbk - Muhammad Naufal; Shodik; Tri Ratnawati; Nekky Rahmiyati (International Journal of Economics (IJEC), 2026)
This study aims to analyze the effect of sustainability disclosure and earning quality on stock prices with dividend policy as a moderating variable at PT Indo Tambangraya Megah Tbk listed on the Indonesia Stock Exchange. This research is motivated by the increasing attention of investors toward non-financial information, particularly related to corporate sustainability aspects, as well as the importance of earnings quality in reflecting the company’s actual financial performance. In addition, dividend policy is considered a signal that can strengthen the relationship between disclosed information and market response. This study employs a quantitative approach with a causal associative research design. The data used are secondary data obtained from annual reports, sustainability reports, and stock price data during the observation period. The data analysis technique uses Moderated Regression Analysis (MRA) processed with the assistance of SPSS. The results of this study are expected to provide empirical evidence regarding the effect of sustainability disclosure and earning quality on stock prices, as well as to explain the role of dividend policy in strengthening or weakening these relationships. This study is expected to contribute to investors, corporate management, and academics in understanding the determinants of stock prices, particularly those related to sustainability and earnings quality